Sur la représentation linguistique de la femme en français et en polonais - Sypnicki, Józef; Dyoniziak, Jolanta (Neophilologica, 2005)
The authors of the article attempted to present the stereotypical image of woman in French and Polish. On the basis of the analysis of the linguistic corpus including two thousand proverbs, idiomatic expressions and metaphors that can be found in various linguistic dictionaries, the authors arrived at the conclusion that in both French and Polish: - the cognitive model of woman comprises three basic profiles (physical aspect, character and intellect traits, social roles), - the metaphoric representation of woman employs items belonging to the women’s domain (home, kitchen), the men’s domain (car, gun), the world of animals (goat, goose, horse) and the imaginary world (goddess, nymph, mermaid), - the stereotypes of women are usually negative, only those concerning mother are deprived of any disparaging elements.